Exotic leptons: Higgs, flavor and collider phenomenology - Altmannshofer, Wolfgang; Bauer, Martin; Carena, Marcela (Journal of high energy physics, 2014)
We study extensions of the standard model by one generation of vector-like leptons with non-standard hypercharges, which allow for a sizable modification of the h → γγ decay rate for new lepton masses in the 300 GeV-1 TeV range. We analyze vacuum stability implications for different hypercharges. Effects in h → Zγ are typically much smaller than in h → γγ, but distinct among the considered hypercharge assignments. Non-standard hypercharges constrain or entirely forbid possible mixing operators with standard model leptons. As a consequence, the leading contributions to the experimentally strongly constrained electric dipole moments of standard model fermions are only generated at the two loop level by the new CP violating sources of the considered setups. We derive the bounds from dipole moments, electro-weak precision observables and lepton flavor violating processes, and discuss their implications. Finally, we examine the production and decay channels of the vector-like leptons at the LHC, and find that signatures with multiple light leptons or taus are already probing interesting regions of parameter space.
Gesehen am 21.11.2017